2016
DOI: 10.1111/tme.12372
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of haemolysis markers following transfusion of uncrossmatched, low‐titre, group O+ whole blood in civilian trauma patients: initial experience at a level 1 trauma centre

Abstract: Administration of ≤2 units of cWB in civilian trauma resuscitation was not associated with clinically significant changes in laboratory haemolysis markers. Efficacy will be determined when larger quantities are transfused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 19 publications
1
106
0
2
Order By: Relevance
“…Detailed information about the logistics of the LTOWB program implemented at this civilian trauma center are presented elsewhere . Briefly, the program was implemented in December 2014 when 2 units of LTOWB were available for transfusion to hypotensive male trauma patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information about the logistics of the LTOWB program implemented at this civilian trauma center are presented elsewhere . Briefly, the program was implemented in December 2014 when 2 units of LTOWB were available for transfusion to hypotensive male trauma patients.…”
Section: Methodsmentioning
confidence: 99%
“…A nongroup O recipient would therefore be at risk of hemolysis from the anti‐A and anti‐B that is contained in the group O whole blood unit itself. It has been demonstrated that the transfusion of up to 4 units of LTOWB to civilian trauma patients did not cause laboratory or clinically apparent changes that were suggestive of hemolysis among the nongroup O recipients compared to the group O recipients . These studies were limited by the nonspecific nature of the changes in the biochemical parameters of hemolysis that occur in trauma patients, and on the blood bank's reliance on a passive reporting mechanism for adverse clinical events related to the LTOWB administration.…”
mentioning
confidence: 99%
“…Group A plasma has been safely used in bleeding trauma patients and “Safety of the use of group A plasma in trauma: the STAT study” showed no difference in clinical outcomes between ABO identical group (A type patients that received A plasma) and ABO minor incompatible group (B/AB patients that received A plasma) . In addition, initial experience with low titer O whole blood units that are given to bleeding trauma patients showed no evidence of hemolysis among nongroup O recipients …”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence that transfusion of stored blood can lead to hemolysis [2931] and so far, there is no evidence that a blood prime causes higher PHb levels. Many of our subjects (45/60, 75%) received a circuit blood prime with no difference in ΔPHb from those who did not.…”
Section: Discussionmentioning
confidence: 99%